Sarcopenia in Type 2 Diabetes Mellitus: A Systematic Review of Prevalence and Impact in Asian Populations - Afifah, Nurul (Universitas Aisyah Pringsewu, 2024)
Sarcopenia and Type 2 Diabetes Mellitus (T2DM) present a significant health burden, particularly within Asian populations. This systematic review aims to explore the prevalence and impact of sarcopenia in Asian individuals with T2DM. Employing a comprehensive literature search in databases like PubMed and Scopus from 2013 to 2023, studies were selected based on strict inclusion and exclusion criteria. The review focuses on the relationship between sarcopenia and T2DM, considering factors such as chronic inflammation, hormonal imbalances, and lifestyle choices. Results from 11 high-quality studies indicate a higher prevalence and risk of sarcopenia in T2DM patients, with a pooled odds ratio of 1.49, suggesting a 49% increased risk in the diabetic population. The findings highlight the need for integrated management strategies and suggest further research into long-term interventions. The study emphasizes the importance of routine sarcopenia screening and a holistic approach to diabetes care that includes diet, exercise, and medication to improve patient outcomes.